Consistent subsets: Computing the Houtman-Maks index in Stata - Per Hjertstrand; Marcos Demetry (Research Institute of Industrial Economics (IFN), 2022)
The Houtman-Maks index is a measure of the size of a violation of utility maximizing (i.e., rational) behavior. This note introduces the Stata command hmindex, which calculates the Houtman-Maks index for a data set of prices and observed choices of a consumer. The command is illustrated with an empirical application.
Keywords: C87; D12; 330; hmindex; Houtman-Maks index; revealed preference; WGARP; WARP